Nutrient cycling and primary production in Peninsular Malaysia waters; regional variation and its causes in the South China Sea. (30th October 2020) - Hee, Yet Yin; Suratman, Suhaimi; Weston, Keith
Abstract: This multidisciplinary survey investigated the combined influence of riverine nutrient input, physical oceanography and monsoon season on water column primary production and nutrient cycling in east coast Peninsular Malaysia waters. Although the combined nutrient load of the regional rivers was similar to major rivers in the northern South China Sea, its influence on primary production was restricted to coastal stations. In the wet season (October–March) the higher riverine nutrient input and a generally well-mixed water column resulted in estimated primary production up to 82.9 μg C L −1 h −1 . During the dry season (April–September) primary production (average 7.3 μg C L −1 h −1 ) was driven by locally upwelled nutrient input in offshore southern waters and Gulf of Thailand-derived input in offshore northern waters. Dry season decoupling of dissolved organic nutrient production and consumption in seasonally stratified offshore waters resulted in its accumulation with the potential to act as a nutrient reservoir. This study therefore provides new insights into how the interplay of physical processes, meteorology and nutrient source influence primary production and associated biogeochemical cycles in this understudied region. Graphical abstract: Image 1 Highlights: Riverine nutrient input influence restricted to coastal area. Combined local riverine nutrient input equivalent to major regional rivers. Gulf of Thailand-derived nutrient input dominated northern offshore area. Upwelling dominated nutrient input to southern offshore area. Nutrient uptake and production decoupling led to offshore nutrient reservoir.